In situ activation graphitization to fabricate hierarchical porous graphitic carbon for supercapacitor - Zhao, Yanling; Zhang, Xiaohua (Scientific reports, 2021)
In situ activation–graphitization method based on the atomically dispersed K and Fe in organic salts is developed to synthesize hierarchical porous graphitic carbon by directly pyrolysis potassium citrate and iron citrate. Moreover, (NH 4 ) 2 C 2 O 4 is also employed as both N dopant and porogen to open up internal structure and regulate pore structure. The inside-out activation leads to the homogeneous reaction and interconnected hierarchical porous structure with few dead pores. Accompanied by high specific surface area, appropriate pore distribution, good conductivity, and N/O functional groups, the sample exhibits high capacitance of 322.6 F g −1 at 0.5 A g −1 , good rate capability, and excellent cycling stability with 101.5% capacitance retention after 15,000 cycles. The supercapacitor shows an energy density of 21.3 W h kg −1 at 456.7 W kg −1 in 1 M Na 2 SO 4 . Easy synthesis, cost-effective, and environmentally benign, the work provides a promising strategy to produce hierarchical porous graphitic carbon applied in energy storage.